Custom-made hinged knee braces with extension support can improve dynamic balance - Akira Ochi; Hiroshi Ohko; Susumu Ota; Nami Shimoichi; Tsukasa Takemoto; Kaho Mitsuke (Elsevier, 2018)
Background/Objective: We investigated whether custom-made hinged knee braces can facilitate knee extensor and flexor strength and influence functional performance as compared with other knee braces. Methods: We enrolled 28 healthy young participants with no history of physical activity or brace use. The participants executed functional performance tests under the following 5 conditions: 1) without a knee brace, 2) wearing a knee sleeve, 3) wearing a hinged knee brace without assistance, 4) wearing a knee brace with extension support (KBE), and 5) wearing a knee brace with flexion support (KBF). The KBE and KBF were custom-made hinged knee braces equipped with rubber tubes. The functional performance tests performed assessed maximal isokinetic strength, single-leg jumping height/distance, anterior and posterior reach distance on a single leg, and dynamic balance ability. Results: The benefit of the custom-made hinged knee brace was observed only during the anterior reach distance on a single leg. The KBE allowed a significantly greater single-leg anterior reach distance when compared to that in the no brace condition. There was a significant relationship between the improvement in the single leg anterior reach distance with KBE and the changes in isokinetic knee extension with KBE compared to the no brace condition. With regard to other parameters, there were no differences compared with the use of other knee braces and thus no apparent benefit. Conclusion: Our findings suggest that using a KBE enhances performance during dynamic balance activity in individuals who benefit from improved knee extension strength.